Efikasi Diri Pada Remaja Tunarungu Berprestasi (Studi Kasus Efikasi Remaja Berkebutuhan Khusus) - Hasneli, Hasneli; Putri, Putri; Khairat, Masnida (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Abstract: This study aims to determine how the description of self-efficacy in deaf adolescents in Nagari Panyalaian, X Koto District, Tanah Datar Regency. This research uses case study method. The data collection techniques in this study were observation, interviews and documentation studies. Based on the results of the study, it is known that firstly in the level aspect, the subject is able to overcome difficult tasks and is able to choose tasks that are more challenging in nature with his limitations he is able to get the title of tourism ambassador despite competing with normal people. Second, on the strength aspect, the subject said that the source of strength to get through a difficult task came from his aspiration to make his parents happy. Third, in the aspect of generality, the subject is able to do assignments in a wide variety of fields and in various situations where the subject is able to become a tourism ambassador for the city of Padang Panjang, dance even though he cannot hear and won a championship in making short films at one of the universities in Padang Panjang.